Characteristics and level of satisfaction of parentes using pediatric teleconsultation during the Covid-19 pandemic - García-Vinatea, Jorge Ricardo (2024)
Objetive: Determine the characteristics and level of satisfaction of parents using pediatric teleconsultation during the COVID-19 pandemic, treated at the Víctor Lazarte Echegaray The sample was made up of 273 parents to whom a user satisfaction survey was conducted by telephone, which consists of 15 questions that were answered based on the Thurstone scale. Results: the level of satisfaction was distributed as high (34.1%), medium (55.3%) and low (10.6%). Most of the patients belonged to the age group of 0-4 years (54.9%), male (54.2%) and resided in the province of Trujillo (67.8%). The parents were mainly aged between 30-39 years (45.8%), were female (90.5%) and had a higher level of education (60%). Teleconsultations had chronic diseases as the main reason for consultation (63.4%), lasted >10 minutes (76.9%), and prescriptions were issued in half of the cases (50.2%). Conclusion: The level of satisfaction of parents using pediatric teleconsultation was mainly at a medium-high level (79.4%). No association was found between the characteristics of the patient, the parent or the teleconsultation with the level of satisfaction.